Fluency and Accuracy in The EFL Oral Expression and Comprehension Classroom - Cherrad Soraya (Journal of Language Education (JoLE), 2023)
Speaking the target language is often defined by both EFL students and teachers as the principal objective of language learning. However, all foreign language teachers recognize that this is in fact, one of the most difficult skills to develop, given that the aim of speaking is hindered by many factors resulting in most being reticent and unforthcoming when asked to speak the target language. Thus, EFL students may have difficulty speaking fluent and accurate English. The present research took place at Djillali Liabes University of Sidi Bel Abbes (Algeria), exactly in English as a foreign language oral classes. It aims to analyze learners' attitudes in the EFL oral expression and comprehension classroom as well as to detect whether the focus on accuracy could hinder the practice of oral communication as well as cause problems in learning. Thus, both classroom observations and an interview were chosen as tools for data collection. Since the aim of language learning is to enhance EFL learners’ oral proficiency, this paper aims to highlight the value of both fluency and accuracy in the EFL oral expression classroom, for the latter to be reached. Keywords: Teaching English as a Foreign Language (TEFL); Foreign Language Learning (FLL); Oral expression and Comprehension classroom, Fluency and Accuracy.